Removal of Basic Blue 3 Dye Using Pomelo Peel - Liew, Shu-Wei; Ong, Siew-Teng (Asian Journal of Chemistry, 2014)
A low-cost adsorbent pomelo peel was investigated for its potential and feasibility to remove basic blue 3 dye from aqueous solutions. Different parameters such as initial dye concentrations, contact time and pH were used to examine its adsorption behaviour. The percentage removal of dye increased as decreasing in the initial dye concentrations and the attainment equilibrium of the adsorption system could be achieved in 4 h. When the experimental data were further studied by the kinetic models, it was evident that the pseudo-second-order kinetic model provided higher correlation coefficient (R2 > 0.9960) for the adsorption system. The effect of solution pH on dye uptake revealed that the percentage removal of dyes increased when the solution pH was increased. Adsorption of basic blue 3 dye onto pomelo peel fitted well to the Freundlich isotherm models, with high correlation coefficient of 0.9914. Based on Langmuir equation, the maximum adsorption capacity of pomelo peel was 23.87 mg/g.